Pengaruh Budaya Organisasi Dan Komitmen Organisasi Terhadap Kinerja Pegawai - Teguh Setiadi; Sri Sundari; Marisi Pakpahan (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2024)
This paper aims to find out about the influence of organizational culture and organizational commitment together on employee performance. performance is the success of an employee's work that has been carried out on the tasks or work assigned to the employee with indicators a. Work quantity includes completing work programs, completing work, making work reports, achieving work quantities, and adjusting work plans; b. Work quality includes developing competence, creating work strategies, having work quality standards, and being motivated to complete the leader's work immediately; c. Efficiency includes the amount of funds provided, working methods, competition with other employees, paying attention to work needs, suitability of work schedules, and completion of work administration; d. Effectiveness, including achieving work targets, utilizing potential, utilizing work time, setting work goals and work responsibilities, and e. Initiative includes several aspects such as the ability to take appropriate steps in the face of difficulties, the ability to do work without assistance, and the ability to take the first step in an activity. There is a positive and very significant influence between organizational culture and organizational commitment together with employee performance.